A glutaredoxin in the mitochondrial intermembrane space has stage-specific functions in the thermo-tolerance and proliferation of African trypanosomes - Ebersoll, Samantha; Musunda, Blessing; Schmenger, Torsten; Dirdjaja, Natalie; Ulrich, Kathrin; Krauth-Siegel, Renate (Redox Biology, 2018)
Trypanosoma brucei glutaredoxin 2 (Grx2) is a dithiol glutaredoxin that is specifically located in the mitochondrial intermembrane space. Bloodstream form parasites lacking Grx2 or both, Grx2 and the cytosolic Grx1, are viable in vitro and infectious to mice suggesting that neither oxidoreductase is needed for survival or infectivity to mammals. A 37°C to 39°C shift changes the cellular redox milieu of bloodstream cells to more oxidizing conditions and induces a significantly stronger growth arrest in wildtype parasites compared to the mutant cells. Grx2-deficient cells ectopically expressing the wildtype form of Grx2 with its C31QFC34 active site, but not the C34S mutant, regain the sensitivity of the parental strain, indicating that the physiological role of Grx2 requires both active site cysteines. In the procyclic insect stage of the parasite, Grx2 is essential. Both alleles can be replaced if procyclic cells ectopically express authentic or C34S, but not C31S/C34S Grx2, pointing to a redox role that relies on a monothiol mechanism. RNA-interference against Grx2 causes a virtually irreversible proliferation defect. The cells adopt an elongated morphology but do not show any significant alteration in the cell cycle. The growth retardation is attenuated by high glucose concentrations. Under these conditions, procyclic cells obtain ATP by substrate level phosphorylation suggesting that Grx2 might regulate a respiratory chain component.